Analyzing the physic-chemical properties of Gallaorol springs is the basis for creating their ecological passport (Uzbekistan) - Tashpulatova S.A.; Turabayev A.N.; Jurayeva O.X. (E3S Web of Conferences, 2024)
Water samples were taken from 12 springs in the Gallaorol district of the Jizzakh region of Uzbekistan, and their physical and chemical properties (odor, color level, cloudy, sediment, clarity, oxygen, demand, oxidability, XPK, alkalinity, acidity, pH, dry residue, Ca2+, Mg2+, Fe, CO32−, HCO3−, SO42−, Cl−, NO2−, NO3−, total hardness, SiO2, J, Br, B, general mineralization, carbon content (organic content), CO2, H2S, K, Na, Mn, Pb, Cu, Cr, Zn, Ni, Co, As, CNS, Al) were thoroughly analyzed in the laboratory of water and the indicators of the results were studied. The results of the research will serve as an important source for the creation of environmental passports of regional springs in the future. Coordinated address pointers presented in the article will be used as important information in the next scientific step in creating special maps of springs in this district and determining route directions. In creating an ecological passport of springs, their physical and chemical results, indicators of coordination measurements, information about their location and the environmental conditions of the spring play a key role.